Empowerment of Retired State Civil Apparatus Through the Smart Enterpreneurship Program by Limited Liability Company (PT) Taspen ( Civil Servant Insurance Savings) Malang - Ajeng Imania; Khrisno Hadi; Muhammad Kamil (Journal of Local Government Issues (LOGOS), 2021)
The Smart Entrepreneur Program is an innovation program from PT. TASPEN (Civil Servant Insurance Savings) is a solution to declining mental and physical health problems and economic problems experienced by retirees when entering retirement. It is because retired State Civil Apparatus (ASN) do not have proper preparation before retiring. Therefore, this program focuses on empowering retired (ASN) so that retirees are more empowered and prosperous and can reduce the possibility of problems when entering retirement. This study uses a qualitative research method with a descriptive approach. In data analysis, researchers used data analysis techniques, according to Creswell. The theory used in this study is the Empowerment theory of Ginanjar Kartasasmita. The research results indicate that the empowerment of ASN through the smart entrepreneurship program conducted by PT. TASPEN  Malang is compatible with the concept of empowerment. In its implementation, three indicators of empowerment are applied: enabling creating conditions that allow for the development of potential retirees, empowering to strengthen the potential of retirees by conducting socialization and training, and finally protecting provided by PT. TASPEN Malang to participants in the smart entrepreneurial program as a form of guarantee given to retirees.